(untitled) (International Journal of Engineering and Computer Science, 2013)
We are currently moving from the Internet society to a mobile society where more and more access to information is done by previously dumb phones. As a result, mobile security is no longer immanent, but imperative. In this paper it shows the various ordinary attacks on Smartphone & the drawback of the techniques at the it show one way to detect the various kind of attacks